Empirical Analysis on the Impact of Regional Allocation of Big Health Industry on Industrial Economic Value Added - Chen, Jun; Wu, Huan; Luo, Xiao (Recent Patents on Engineering, 2024)
Background: With the development of economic society, people’s demand for big health products is also growing. At the same time, the uncertainty of big healthy enterprises’ operations is increasing, and the internal factors affecting enterprise performance are also increasing. Methods: Based on the data from 2010 to 2020 of 329 listed big health products companies in China, this paper adopts a fixed effect regression model to empirically analyze the relationship among marketing/ sale expenditure, R expenditure, and economic value added of big health enterprises. The moderating effect of economic level and population size on the model is discussed by grouping regression. Results: The results show that: In the long run, R investment and marketing/ sale investment can significantly promote the growth of the overall value of China’s big health enterprises, and the promotion effect lags. Conclusion: The big business enterprise of health investment in R and marketing/ sale of enterprise development is affected by the business area location, such as R and marketing/ sale spending in big cities can promote enterprise economic value added, and the small city marketing/ sale into obvious economic value added of the enterprise itself. Still, the R investment in the small city has no significant correlation with enterprise economic value added.
Keywords: big health industry